Developments in American Politics 9
XIX, 346 p. 21 illus., 13 illus. in color.
Keywords: This textbook provides students of US Politics with an informed scholarly analysis of recent developments in the American political environment, using historical background to contextualize contemporary issues. As the ninth edition, this book reviews a time of political controversy in the United States, touching on topics such as gender, economic policy, gun control, immigration, the media, healthcare, the COVID-19 pandemic, and the widespread social protests against police brutality. The book looks both backwards to Trump's presidency and forward to Biden's. Ultimately, the editors and contributors evaluate the significance of these events on the future of American politics, providing a perspective that is at once broad and meticulous. Gillian Peele is Emeritus Fellow of Lady Margaret Hall, University of Oxford, UK. Bruce E. Cain is Charles Louis Ducommun Professor in Humanities and Sciences and Director of the Bill Lane Center for the American West at Stanford University, USA. Jon Herbert is Senior Lecturer in US Politics at Keele University, UK. Andrew Wroe is Senior Lecturer in American Politics at the University of Kent, UK.